2013
DOI: 10.1111/ejn.12392
|View full text |Cite
|
Sign up to set email alerts
|

TMS reveals a direct influence of spinal projections from human SMAp on precise force production

Abstract: The corticospinal (CS) system plays an important role in fine motor control, especially in precision grip tasks. Although the primary motor cortex (M1) is the main source of the CS projections, other projections have been found, especially from the supplementary motor area proper (SMAp). To study the characteristics of these CS projections from SMAp, we compared muscle responses of an intrinsic hand muscle (FDI) evoked by stimulation of human M1 and SMAp during an isometric static low-force control task. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Micro stimulation of the primary motor cortex in rhesus macaques generated both facilitatory and suppression effects in both flexor and extensor muscles of the distal and proximal forearm (Park et al, 2004); which is a response presumably mediated through the CST. Transcranial magnetic stimulation of the supplementary and primary motor areas during isometric static hand force task produced EMG effects with similar amplitude and latencies recorded from the intrinsic hand muscles, suggesting that both cortical areas effectively control the spinal cord excitability (Entakli et al, 2013). Indeed, many areas of the neocortex send projections to the spinal cord through the CST.…”
Section: Introductionmentioning
confidence: 99%
“…Micro stimulation of the primary motor cortex in rhesus macaques generated both facilitatory and suppression effects in both flexor and extensor muscles of the distal and proximal forearm (Park et al, 2004); which is a response presumably mediated through the CST. Transcranial magnetic stimulation of the supplementary and primary motor areas during isometric static hand force task produced EMG effects with similar amplitude and latencies recorded from the intrinsic hand muscles, suggesting that both cortical areas effectively control the spinal cord excitability (Entakli et al, 2013). Indeed, many areas of the neocortex send projections to the spinal cord through the CST.…”
Section: Introductionmentioning
confidence: 99%
“…The SMA is a secondary motor area that plays a pivotal role in complex hand movements ( Shirota et al, 2012 ). SMA and M1 both have a direct influence on force production during fine manual motor tasks ( Entakli et al, 2014 ). A previous study using fMRI also found a correlation between task-related brain activation patterns and final motor status.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly though, other observations question the validity of this assumption. Indeed, like M1, SMA also presents pyramidal cells that project to the spine (Dum and Strick 1996) and in specific contexts, a unique stimulation of SMA with single-pulse TMS can evoke MEPs (Entakli et al 2014;Spieser et al 2013), indicating that these pyramidal cells can also recruit motoneurons. Thus, it is possible that the MEP potentiation reported in ppTMS studies using short intervals reflects the summation of volleys descending from SMA and M1 and converging at close times on motoneurons.…”
Section: Introductionmentioning
confidence: 99%